Personal Branding Food Vlogger Dimas Angga Melalui Sosial Media Instagram @njajantok_sby - Sertiana, Indira; Setianingrum, Vinda Maya (Universitas Negeri Surabaya, 2025)
With the increasing use of the internet and social media, Dimas Angga utilizes Instagram to review various foods, primarily focusing on local cuisine with his distinctive style. This study aims to describe the personal branding of food vlogger Dimas Angga through his Instagram account, @njajantok_sby. This research is qualitative and uses a case study method. Data were collected through in-depth interviews with Dimas Angga, his manager and videographer team, two followers of the @njajantok_sby Instagram account, as well as documentation and direct observation of his activities on Instagram. The study employs Petter Montoya's personal branding theory, which includes eight key concepts. The findings indicate that Dimas Angga has successfully built a strong personal brand by applying the concepts of specialization and personality, showcasing his unique style with polite eating habits, avoiding excessive trends like mukbang, focusing on street vendors, delivering detailed information, and maintaining a consistent and authentic personality in his content. This approach has not only increased his popularity among Instagram users but has also attracted collaborations with brands in the culinary field. Keywords: Personal branding, Food Vlogger, Social Media, Instagram.